Effects of exercise on carotid arterial wall thickness in obese pediatric populations: A meta-analysis of randomized controlled trials (2017)
Background: In pediatric populations, the use of carotid intima-media thickness (IMT) as a marker of cardiovascular risk has increased. However, previous studies examining the effects of exercise training on arterial structure and function in obese children and adolescents have shown inconsistent findings. The primary aim of this systematic review and meta-analysis is to expand on the current body of literature by providing a quantitative estimate of the change in carotid IMT following exercise training as well as to provide an exploratory analysis of potential moderators associated with the variation in response to an exercise training intervention in overweight and obese youth. Materials and Methods: A computerized search was made using three databases. The analysis was restricted to studies that examined the effect of exercise interventions on carotid IMT in pediatric obesity (6-18-year-olds). Hedges' g and 95% confidence intervals (CIs) were calculated. Results: Six randomized controlled trials (303 youths) were included. Exercise was associated with a small-to-moderate but significant reduction in carotid IMT (g = -0.306; 95% CI -0.540 to -0.072; p = 0.011). Likewise, exercise program duration per week significantly influenced the effect of exercise on carotid IMT (? = -0.060; p = 0.015). Conclusions: Exercise seems to reduce carotid IMT in childhood obesity. Therefore, encouraging obese pediatric individuals to become physically active can lead to favorable changes in the arterial wall. © Copyright 2017, Mary Ann Liebert, Inc.